A note on the attenuation of the sommerfeld effect of a non-ideal system taking into account a MR damper and the complete model of a DC motor - Castao, Kleber A. L.; Goes, Luis C. S.; Balthazar, José Manoel [UNESP] (Sage Publications Ltd, 2011)
The main purpose of this paper is to study the attenuation of the jump phenomena associated with the Sommerfeld Effect introduced by the nonlinearities of a magnetic rheological damper (MRD) in a non-ideal vibrational system, excited by a DC motor modeled as limited power source. Numerical simulations of the nonlinear vibrations of the system are carried out for different values of the MRD control parameter in order to show the amplitude reduction of the vibrations close to the system resonance introduced by the nonlinear damping effect of the MR system.
Keywords: MR damper; non-ideal system; Sommerfeld Effect